Antidepressant-Like Effect and Mechanism of Ginsenoside Rd on Rodent Models of Depression - Li Y; Wang ML; Zhang B; Fan XX; Tang Q; Yu X; Li LN; Fan AR; Chang HS; Zhang LZ (Dove Medical Press, 2022)
Yu Li,1,* Mei-Ling Wang,1,* Bo Zhang,1 Xiao-Xu Fan,1 Qin Tang,1 Xue Yu,2 Li-Na Li,2 Ang-Ran Fan,2 Hong-Sheng Chang,1 Lan-Zhen Zhang1 1School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing, 102488, People's Republic of China; 2School of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 102488, People's Republic of China*These authors contributed equally to this workCorrespondence: Lan-Zhen Zhang; Hong-Sheng Chang, School of Chinese Materia Medica, Beijing University of Chinese Medicine, Northeast Corner of the Intersection of Sunshine South Street and Baiyang East Road, Fangshan District, Beijing, 102488, People's Republic of China, Tel +86 10 5391 2122, Email zhanglanzhen01@126.com; chs1971@sina.comBackground: There is growing evidence to suggest that ginsenoside Rd (GRd) has a therapeutic effect on depression, but the specific mechanisms behind its activity require further study.Objective: This study is designed to investigate the antidepressant-like effect and underlying mechanisms of GRd.Methods: In this study, the behavioral despair mouse model of depression and chronic unpredictable mild stress (CUMS) rat model of depression were established to explore the effects of GRd on depression-like behavior and its underlying mechanisms. Behavioral tests were used to evaluate the replication of animal models and depression-like behaviors. The hypoxia-inducible factor-1α (HIF-1α) blocker 2-methoxyestradiol (2-ME) was injected to determine the role of HIF-1α in the antidepressant-like effect of GRd. In addition, molecular biology techniques were used to determine the mRNA and protein expression of HIF-1ɑ signaling pathway and synaptic plasticity-related regulators, that is synapsin 1 (SYN 1) and postsynaptic density protein 95 (PSD 95). In silico binding interaction studies of GRd with focused target proteins were performed using molecular docking to predict the affinity and optimal binding mode between ligands and receptors.Results: Our data show that GRd significantly reversed depression-like behavior and promoted mRNA and protein expression of HIF-1ɑ signaling pathway and synaptic plasticity-related regulators. However, the antidepressant-like effect of GRd disappeared upon inhibition of HIF-1α expression following administration of 2-ME. Furthermore, molecular docking results showed that GRd possessed significant binding affinity for HIF-1α, VEGF, and VEGFR-2.Conclusion: Our results show that GRd exhibits significant antidepressant-like effect and that HIF-1α signaling pathway is a promising target for the treatment of depression.Keywords: ginsenoside Rd, antidepressant effect, HIF-1α-VEGF signaling pathway, VEGFR-2, synaptic plasticity-related regulators, molecular docking